Operational Management in Work Program Development at Al-Irsyad Parepare Mosque - Rosmilasari Rosmilasari; Nurhikmah Nurhikmah; Muhammad Haramain (Jurnal Kajian Manajemen Dakwah, 2022)
This study aims to determine operational management in developing work programs as well as supporting and inhibiting factors for mosque management in developing work programs at the Al-Irsyad Ujung Baru mosque, Parepare City. The type of research used is descriptive qualitative research. Conducting research at the Al-Irsyad Ujung Baru Mosque, Parepare City with sources from the chairman of the mosque management, mosque imam, mosque adviser and three members of the Al-Irsyad mosque. Data collection techniques using interviews, observation and documentation. The types and sources of data used in this study are primary data and secondary data. Data analysis used by researchers is data reduction and data presentation. The results of this study indicate that operational management in the development of work programs, namely operational planning, facility inventory, management administration, integrated quality control, facility maintenance and network designing techniques which are very helpful in developing work programs at the Al-Irsyad mosque.